Exacerbation of Psoriasis Vulgaris Induced by Vaccine COVID-19 in HIV Patient: A Case Report - Gardenia Akhyar; I. Izrul; M. Ashar (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Psoriasis is a chronic and inﬂammatory skin disease. Many triggering factors can cause exacerbation of psoriasis, such as infection, trauma, and drugs. Several vaccines are known to cause new lesions or exacerbation of psoriasis, including Bacillus Calmette-Guerin (BCG), influenza, tetanus-diphtheria, and pneumococcal polysaccharide. In the COVID-19 pandemic, the COVID-19 vaccine is known to cause the appearance of new lesions or exacerbation of psoriasis. Case presentation: A woman, 31 years old, came to the clinic with itchy reddish patches with white scales on her face, chest, stomach, back, arms, and both legs, and increased since 2 weeks ago. Previously, the patient got the first COVID-19 vaccine (Sinovac), and three days later, red patches appeared with white scales on the chest, stomach, and back. The patient had been diagnosed with psoriasis 3 years ago. Dermatology examination showed reddish patches with white scales on the face, chest, stomach, back, arms, and both legs. Auspitz sign and Kaarvetsvlek phenomen were positive. PASI score was 9,2. Dermoscopy examination showed red dot distribution on light pink background and white scales. She was treated with desoximetasone cream 0,05% twice a day and cetirizine tablet 10 mg once a day. After 2 months of therapy, reddish patches were decreased, and the PASI score was 6,9. Conclusion: COVID-19 vaccine can cause exacerbations in psoriasis patients, but this vaccine can still be given to psoriasis patients. It is based on the documented eﬃcacy of the COVID-19 vaccine in the prevention of severe COVID-19 infection and fatality. Psoriasis patients should be consulted before getting vaccinated for COVID-19, and prompt clinical visits should be available if exacerbation develops.